Answered

At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Find the 6th term in the expanded form of the equation (2x+y)^9

Sagot :

[tex]T_r={n \choose r-1}a^{n-(r-1)}b^{r-1}\\ T_6={9 \choose 6-1}(2x)^{9-(6-1)}y^{6-1}\\ T_6={9 \choose 5}(2x)^4y^{5}\\ T_6=\frac{9!}{5!4!}16x^4y^{5}\\ T_6=\frac{6\cdot7\cdot8\cdot9}{2\cdot3\cdot4}16x^4y^{5}\\ T_6=7\cdot2\cdot9\cdot16x^4y^{5}\\ T_6=2016x^4y^5[/tex]
[tex]Use\ the\ Pascal's\ Triangle\ (look\ at\ the\ picture)\\\\6-th\ term\ of\ (2x+y)^9\ is\\\\ 126(2x)^4y^5=126\times16x^4y^5=2016x^4y^5[/tex]
View image Аноним
View image Аноним